Partisipasi Masyarakat dalam Penggunaan Aplikasi E-Peken di Sentra Wisata Kuliner Semolowaru Kota Surabaya - Nizar, Emirul Ibnu; Alves, Vintya Meily; Willyanto, Andre; Aisyah, Farsya Audria; Nawangsari, Ertien Rining (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The E-Peken application is a digital innovation developed by the Surabaya City Government to support the digitalization of MSMEs, especially in the Semolowaru Culinary Tourism Center (SWK). This study aims to analyze community participation in using the E-Peken application as an effort to improve marketing and operational efficiency of MSMEs. The results show that community participation, both traders and consumers, is still low due to the lack of socialization, training, and mentoring from the government and urban village. In addition, the lack of digital literacy among traders and the limited promotion of the application have caused the use of E-Peken to not be optimal. This study provides strategic measures, such as community-based training, more intensive promotional campaigns, and incentivizing active users of the application. With a coordinated approach, E-Peken can become a leading platform in supporting the digitalization of MSMEs and strengthening the local economy in Surabaya.